A Multidimensional Exercise Program in the Home for Older Adults Designed to Improve Function. Issue 3 (August 2019) - Whitney, Susan L.; Ellis, Jennifer; Otis, Laurie; Marchetti, Gregory
The purpose of this study was to determine whether there was difference in the OASIS (Outcome and Assessment Information Set) activities of daily living (ADL) items scores between the Safe Strides program and Safe Strides plus Zōntago program. Eight home care offices were selected for this prospective randomized quality improvement study where Safe Strides versus Safe Strides plus Zōntago were compared. Rehabilitation outcome OASIS ADL change scores were analyzed for 112 total patient care episodes. The Safe Strides + Zōntago mean total ADL score change and ADL change per visit were higher than the Safe Strides group. Differences in ADL outcomes in older adults undergoing home care provided by physical therapists and physical therapist assistants in the Safe Strides exercise program versus the Safe Strides plus Zōntago program were noted. The Safe Strides + Zōntago compared with Safe Strides alone improved patient functional outcomes as measured by the OASIS.